Additive manufacturing of micropatterned functional surfaces: a review - Chivate, Aditya; Zhou, Chi (International Journal of Extreme Manufacturing, 2024)
Over the course of millions of years, nature has evolved to ensure survival and presents us with a myriad of functional surfaces and structures that can boast high efficiency, multifunctionality, and sustainability. What makes these surfaces particularly practical and effective is the intricate micropatterning that enables selective interactions with microstructures. Most of these structures have been realized in the laboratory environment using numerous fabrication techniques by tailoring specific surface properties. Of the available manufacturing methods, additive manufacturing (AM) has created opportunities for fabricating these structures as the complex architectures of the naturally occurring microstructures far exceed the traditional ways. This paper presents a concise overview of the fundamentals of such patterned microstructured surfaces, their fabrication techniques, and diverse applications. A comprehensive evaluation of micro fabrication methods is conducted, delving into their respective strengths and limitations. Greater emphasis is placed on AM processes like inkjet printing and micro digital light projection printing due to the intrinsic advantages of these processes to additively fabricate high resolution structures with high fidelity and precision. The paper explores the various advancements in these processes in relation to their use in microfabrication and also presents the recent trends in applications like the fabrication of microlens arrays, microneedles, and tissue scaffolds. Provide a comprehensive overview of the different micromanufacturing techniques with a detailed focus on drop-on-demand (DOD) inkjet printing and DLP based printing. Introduce the working principles of DOD inkjet printing and DLP printing and discuss the current status pertaining to micro fabrication. Summarize notable applications of DOD and DLP based printing technology at micro scales. Discuss the following challenges, limitations and offer valuable insights and prospects into the current state of DLP based and DOD inkjet printing technology.